Keeping together: older people in longitudinal research studies, the case of TwinsUK. Issue 2 (8th September 2020) - Mein, Gill; Bhatti, Taha; Bailey, Sarah; Steves, Claire J.; Hart, Deborah; Garcia, Paz; Tinker, Anthea
Abstract : Purpose: A decline in participation in research studies as people age is inevitable as health declines. This paper aims to address this by collecting data from a group of participants to examine their reasons for declining attendance and suggestions for maintaining attendance as participants age. Design/methodology/approach: This research used a postal self-completed questionnaire including open and closed questions. The questionnaire was sent to those participants who have declined to attend further clinic visits. Results were analysed using thematic content analysis. Findings: The study had a 51% response rate. Participants reported difficulty with travelling to the clinic, and health as the main issues in addition to family demands and a lack of understanding regarding the continuing participation of a singleton twin. Research limitations/implications: This study could only include data from responding participants, answers to open question also included comments from participants regarding their twin. Practical implications: An anonymous questionnaire was sent to all individuals in the Keeping Together project. It was therefore not possible to identify if responses were from both members of a twin pair. Originality/value: Maintaining participation in longitudinal studies is of crucial importance to enhance the value of data. Retention of participants in studies may change as people age and health becomes impaired. Suggestions for maintaining and improving the retention of older participants have been identified and are generalisable to other longitudinal studies of ageing.